Current Nervous System Related Drug Targets for the Treatment of Amyotrophic Lateral Sclerosis - C. Pawlyk, Aaron; A. Cassel, Joel; B. Reitz, Allen (Current Pharmaceutical Design, 2010)
Amyotrophic lateral sclerosis (ALS) is a debilitating and ultimately fatal indication that is the most prevalent adult-onset motoneuron disorder. ALS imparts tremendous suffering upon patients and caregivers alike. Exciting new insight has been obtained as to the etiology and initiation of the disease during the past decade, particularly affecting the larger, sporadic patient population. An important new discovery is the involvement of the TAR DNA binding protein (TDP-43) based upon genetic evidence and the presence of the cytosolic ubiquitinylated TDP-43 aggregates found during post-mortem analysis of damaged motoneuron in the spinal cord of ALS patients. Superoxide dismutase (SOD1) continues to be of interest for the ∼20% of the familial ALS patients who have the inherited form of the disease (∼15% of the total), but SOD1 does not appear to be as relevant as was once imagined for the sporadic patient population. We can now target specific biochemical pathways and deficits via traditional drug discovery efforts and may thus be able to achieve more effective therapeutic relief for patients who suffer from this disease. In this review we present a comprehensive discussion of current molecular targets and pathways that are of interest to small molecule drug discovery efforts for the treatment of ALS.
Keywords: drug targets